REASONS FOR NORMALIZING DIPLOMATIC RELATIONS BETWEEN ISRAEL AND THE UNITED ARAB EMIRATES AND BAHRAIN THROUGH THE ABRAHAM ACCORD AGREEMENT - Batari Kani Raras (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This research examines the reasons for the normalization of diplomatic relations between Israel and United Arab Emirates and Bahrain. The normalization of diplomatic relations was marked by the ratification of the Abraham Accord agreement as a form of the Israeli state's efforts to seek an alliance with Arab countries, namely the United Arab Emirates and Bahrain. This agreement was ratified by signing by Donald Trump as the President of the United States as well as the host, Prime Minister of Israel Benjamin Netanyahu, Minister of Foreign Affairs of the UAE Abdullah Bin Zayed Al-Nahyan, Minister of Foreign Affairs of Bahrain Abdullatif Al-Zayani at the White House Washington DC on 15 September 2020 . This study uses a qualitative method, with data collection techniques through literature study sourced from several books, journals, final assignments, documents and websites. This study uses the Regional Security Complex theory by Barry Buzan which defines that the state as a political actor will establish relations with other countries if they have the same security problems so that common interests and dependencies will be established between these countries. Iran is present as a threat to the Middle East region so that in this case Israel establishes its alliance with the United Arab Emirates and Bahrain as a safeguard in order to maintain regional security stability. The results of this paper conclude that the normalization carried out by Israel with the United Arab Emirates and Bahrain through the Abraham Accord agreement is motivated by reasons: Deterring the threat of Iranian power, Becoming a partner in military cooperation, and Optimizing economic cooperation. Keyword: Abraham Accords, Middle East Stabilization, Normalization, Regional Security Complex